Urban living laboratories: Conducting the experimental city?. (October 2019) - Bulkeley, Harriet; Marvin, Simon; Palgan, Yuliya Voytenko; McCormick, Kes; Breitfuss-Loidl, Marija; Mai, Lindsay; von Wirth, Timo; Frantzeskaki, Niki
The recent upsurge of interest in the experimental city as an arena within and through which urban sustainability is governed marks not only the emergence of the proliferation of forms of experimentation – from novel governance arrangements to demonstration projects, transition management processes to grassroots innovations – but also an increasing sensibility amongst the research community that urban interventions can be considered in experimental terms. Yet as research has progressed, it has become clear that experimentation is not a singular phenomenon that can be readily understood using any one conceptual entry point. In this paper, we focus on one particular mode of experimentation – the urban living laboratory (ULL) – and develop a typology through which to undertake a comparative analysis of 40 European ULLs, to understand how and why such forms of experimentation are being designed and implemented, and to identify the particular forms of experimentation they entail. We argue that there are distinct types of ULL taking shape, delimited by the ways in which they are designed and deployed through, on the one hand, specific kinds of configuration and practice and, on the other hand, by the ways in which they take laboratory form: the different dispositions towards the laboratory they entail. We propose three 'ideal' ULL types – strategic, civic and organic – and argue that these can be placed along the spectrum of four dispositions: trial, enclave, demonstration and platform.